IMPLEMENTASI DIVERSI OLEH PENYIDIK TERHADAP ANAK SEBAGAI PELAKU TINDAK PIDANA MENURUT UNDANG-UNDANG NOMOR 11 TAHUN 2012 TENTANG SISTEM PERADILAN PIDANA ANAK DI POLRES PASAMAN - Ronaldfri wiliam, Darlisma, (LPPM Universitas Muhammadiyah Sumatera Barat, 2018)
Diversion is the transfer of the settlement of the Child's case from the criminaljustice process to a process outside the criminal justice. At the level of investigation,prosecution, and examination of cases of children in the district court Diversion must besought. Diversion carried out in the event that a crime is carried out is threatened withimprisonment under seven years and is not a repeat of a criminal act. The purpose of thisstudy was to examine the implementation of Diversion conducted by Investigators onChildren as Actors of Criminal Acts and examine what obstacles faced by investigators inimplementing Diversion on Children as Actors of Crime. The research was carried outwith empirical juridical research methods. Empirical juridical research is legal researchconducted to find solutions to problems of legal problems that contain the gap betweenreality and what should be. Based on the results of the study it was found that theimplementation of diversion by investigators in completing criminal cases committed bychildren in Pasaman Regency has not been carried out in accordance with Law Number 11of 2012 concerning the Juvenile Justice System and is more likely to use the RestorativeJustice method / settlement of criminal cases with involving the perpetrator, victim, familyof the perpetrator or victim, and other related parties to jointly seek settlement. This is dueto the lack of supporting facilities and infrastructure so that it greatly influences theperformance of female and child service personnel in carrying out their duties ininvestigating cases related to children.Keywords: Diversion Implementation, Investigator, Child, Criminal Act